2021
DOI: 10.1097/mlr.0000000000001335
|View full text |Cite
|
Sign up to set email alerts
|

Design Considerations for the Development and Implementation of a Medical Respite for Older Adults Experiencing Homelessness in Metro Vancouver

Abstract: Background: Older persons with lived or living experience of homelessness (PWLEs) often live with complex physical and/or mental health conditions which are challenged by poor access to health services, especially primary care. To fill the gap in the continuum of care following hospital discharge for PWLEs, medical respite provides health and shelter support for PWLEs who do not have acute care needs that qualify for a stay in a hospital bed, yet are too sick or frail to recover on the streets or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition to immediate recovery, medical respite programs provide opportunities for positive lifestyle changes (Pedersen et al, 2018). Notably, the physical design of the program space may be less important than the program features that enable 24/7 rest and support from a case manager, as evidenced in the present study and elsewhere (Canham et al, 2021;Ciambrone & Edgington, 2009).…”
Section: Discussionmentioning
confidence: 69%
“…In addition to immediate recovery, medical respite programs provide opportunities for positive lifestyle changes (Pedersen et al, 2018). Notably, the physical design of the program space may be less important than the program features that enable 24/7 rest and support from a case manager, as evidenced in the present study and elsewhere (Canham et al, 2021;Ciambrone & Edgington, 2009).…”
Section: Discussionmentioning
confidence: 69%
“…Providers and OPEH alike reported desires for peer‐led programs and participatory design principles, complementing existing research (Canham, Humphries, Danielsen, et al, 2021). Although little evidence exists for OPEH, previous research has found peer‐led interventions and support to be beneficial for younger adults experiencing homelessness (Holland et al, 2016; Miler et al, 2020).…”
Section: Discussionmentioning
confidence: 79%
“…The barriers to health experienced by the participants combined with severely limited housing options highlight an urgent need for dedicated programming designed to take care of people experiencing both complex medical needs and housing instability. Expanding programs like medical respite and permanent supportive housing have been shown to be successful in achieving those goals (Canham et al., 2021; Kinczewski et al., 2021). In addition, this study highlights the gap in prevention services for those at risk for homelessness, as a onetime response to an ongoing problem, is not sufficient.…”
Section: Discussionmentioning
confidence: 99%